Eksistensi Kesultanan Banten Di Lampung Barat Abad XVIII Berdasarkan Naskah Dalung Sukau - Karsiwan Karsiwan; Lisa Retno Sari; Gaya Mentari; Hidayat Mohamad Wahyu; Wellfarina Hamer (PURBAWIDYA, 2026)
The global demand for pepper at the end of the 17th century led the Sultanate of Banten to attempt to expand its influence on Lampung. Tthis study aims to determine the influence of Banten on the expansion of black pepper cultivation through a study of the Sukau dalung in West Lampung. The method used in this study is the historical method with four stages, namely heuristics, source criticism, interpretation, and historiography. The primary source was the Sukau dalung, and the secondary sources were books, manuscripts, and articles related to the Sukau dalung and black pepper cultivation during the Banten Sultanate. The Sukau dalung was an agreement on pepper cultivation between the Banten Sultanate and the traditional leader of Buay Nyerupa, who was based in Tapak Siring in the Sukau region of West Lampung. This dalung was issued during the reign of Sultan Abdul Mahasin Muhammad Zainal Abidin in 1692. The dalung manuscript contains agreements on, among other things, the position of Punggawa, rules on debt and credit, the obligation to plant 500 pepper plants, pepper trade transactions, taxes and rules on travelling to and from Lampung, and a ban on war between fellow Lampung people. The Sukau Dalung, from the perspective of Gramsci's theory of hegemony, is a tool for legitimising Banten's power over a region through political and cultural work by granting a few attributes and titles, as well as spreading Islamic ideology in West Lampung.